PSVII-31 Impact of Total Dissolved Solids (TDS) in Drinking Water on Nursery Pig Performance - Samuel, Ryan S (J Anim Sci, 2020)
High concentrations of total dissolved solids (TDS) in water have been reported to increase the incidence of diarrhea and reduce nursery pig growth performance. The particular minerals of concern for pigs are typically intakes of magnesium and sodium sulfate salts. Therefore, the objective of this study was to investigate the effects of drinking water with added concentrations of TDS from sulfate salts on animal performance and feed and water disappearance. Newly weaned pigs (n = 1,144; 20 d old PIC) were stocked at 26 pigs per pen of equal gender in 44 pens in a wean-to-finish commercial research barn. Each pen was randomly assigned to receive one of four water treatments into two cup waters per pen: 1) combination of CaSO(4), MgSO(4), and NaSO(4); 2) CaSO(4); 3) MgSO(4); 4) NaSO(4). The drinking water treatments were derived from stock solutions delivered at 1:128 to relevant pens using a separate medicator per water line (Table 1). Pigs were provided free access to four phase nursery diets and water throughout the trial. Pen weights were measured on d 0, 7, 21, 35, and 42 using a scale that weighs the entire pen of pigs. Feed remaining on weigh days was calculated according to a prepared calibration curve by measuring the distance from the top of the feeder to the top of the feed. Water meters at each pen were read on weigh days to determine the water disappearance per pen. Water treatment did not affect (P > 0.07) ADG nor ADFI of nursery pigs. Water disappearance tended to be greater (P = 0.10) in pens receiving the CaSO(4) water compared to the combination treatment from d 21 to 35. The TDS concentrations from sulfate complexes used in this experiment did not impact the growth performance or feed or water disappearance of newly weaned nursery pigs. [Image: see text]